First observation of strange baryon enhancement with effective energy in pp collisions at the LHC - The ALICE collaboration; S. Acharya; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics)
Abstract The production of (multi-)strange hadrons is measured at midrapidity in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV as a function of the local charged-particle multiplicity in the pseudorapidity interval |η| < 0.5 and of the very-forward energy measured by the ALICE Zero-Degree Calorimeters. The latter provides information on the effective energy, i.e. the energy available for particle production in the collision once subtracted from the centre-of-mass energy. The yields of K S 0 $$ K_{S}^0 $$ , Λ + Λ ¯ $$ Λ +\overline{Λ} $$ , and Ξ − + Ξ ¯ + $$ Ξ^{-}+{\overline{Ξ}}^{+} $$ per charged-particle increase with the effective energy. In addition, this work exploits a multi-differential approach to decouple the roles of local multiplicity and effective energy in such an enhancement. The results presented in this article provide new insights into the interplay between global properties of the collision, such as the initial available energy in the event, and the locally produced final hadronic state, connected to the charged-particle multiplicity at midrapidity. Notably, a strong increase of strange baryon production with effective energy is observed for fixed charged-particle multiplicity at midrapidity. These results are discussed within the context of existing phenomenological models of hadronisation implemented in different tunes of the PYTHIA 8 event generator.